Depletion of CD11c+ cell attenuates progression of abdominal aortic aneurysm. (3rd January 2020) - Okuno, Keisuke; Cicalese, Stephanie; Eguchi, Satoru
Abstract: Chronic inflammation of the arterial wall has been implicated in the development of abdominal aortic aneurysm (AAA). However, the detailed molecular mechanism(s) by which inflammatory cells contributes to AAA pathogenesis remains largely unclear. In their article in Clinical Science, Krishna et al. have reported that depletion of CD11c + dendritic cells inhibited experimental AAA formation in mice. The authors also demonstrated a decrease in CD4 and CD8 positive T cells in the circulation, lower plasma neutrophil elastase activity, and aortic matrix remodeling. These novel findings will help clarify the underlying mechanisms of AAA progression and may provide a new target for future therapeutic research in AAA formation.